Explaining community capital changes for malaysian negritos based on longitudinal panel study. Issue 3 (27th May 2022) - Amir Zal, W. A.; Che Daud, Burhan; Omar, Mustaffa; Salleh, Hood; Halim, Sharina Abdul
ABSTRACT: It is difficult to understand the changes in the community development process among Negritos in Malaysia without comprehensive data in a longitudinal framework. Thus, this study attempts to explain those changes through just such a study. The format adopts a quantitative approach to a survey designed for Negrito heads of households (HoH). The finding show a change happening in the community capitals, especially the human, social and cultural capitals. But other community capitals have not changed. Two main implications are highlighted: (1) the patterns of change among Negrito are revealed, community capitals under their control are changing, and (2) comprehensive data about the changes can only be obtained through a longitudinal panel study. Thus, longitudinal panel studies should be practiced by researchers in future, which is driving the need for massive and accurate data to develop a community.